2018
DOI: 10.1016/j.molcel.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Organization of Single mRNPs at Different Stages of the Gene Expression Pathway

Abstract: Summary mRNAs form ribonucleoprotein complexes (mRNPs) by association with proteins that are crucial for mRNA metabolism. While the mRNP proteome has been well characterized, little is known about mRNP organization. Using a single molecule approach, we show that mRNA conformation changes depending on its cellular localization and translational state. Compared to nuclear mRNPs and lncRNPs, association with ribosomes decompacts individual mRNAs, while pharmacologically dissociating ribosomes or sequestering them… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
174
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(205 citation statements)
references
References 76 publications
31
174
0
Order By: Relevance
“…However, the versatility of the mRNA circularization has been challenged recently by the indications that the closed-loop conformation is rarely observed in living mammalian cells under normal conditions [69,70], that the predominant form of actively translated mRNA is likely not circularized in yeast and mammals [16,71], and that the polysome topology in a plant cell-free system undergoes complicated step-wise evolution accompanied by translation efficiency changes [72,73]. On the other hand, new evidence of functional mRNA cyclization came from recent studies of m 6 A mRNA methylation that brings 5 and 3 UTRs together via eIF3h-METTL3 interaction and/or cap/eIF4F/eIF3/YTHDF1/m6A bridge formation, which facilitates translation during oncogenesis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the versatility of the mRNA circularization has been challenged recently by the indications that the closed-loop conformation is rarely observed in living mammalian cells under normal conditions [69,70], that the predominant form of actively translated mRNA is likely not circularized in yeast and mammals [16,71], and that the polysome topology in a plant cell-free system undergoes complicated step-wise evolution accompanied by translation efficiency changes [72,73]. On the other hand, new evidence of functional mRNA cyclization came from recent studies of m 6 A mRNA methylation that brings 5 and 3 UTRs together via eIF3h-METTL3 interaction and/or cap/eIF4F/eIF3/YTHDF1/m6A bridge formation, which facilitates translation during oncogenesis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Another line of evidence comes from single-molecule-resolution fluorescent in situ hybridization (smFISH) imaging studies in human cells. The median distance between the 5' and 3' ends of actively translated mRNAs, with lengths from 6,000 to 18,000 nucleotides, was 100-200 nm (Adivarahan et al, 2018;Khong & Parker, 2018). By contrast, the 5' and 3' ends in these mRNAs co-localized when translation was inhibited with arsenite or the antibiotic puromycin (Adivarahan et al, 2018;Khong & Parker, 2018).…”
Section: Mrna Compactness and The Closed-loop Model Of Translation Inmentioning
confidence: 95%
“…By contrast, the 5' and 3' ends in these mRNAs co-localized when translation was inhibited with arsenite or the antibiotic puromycin (Adivarahan et al, 2018;Khong & Parker, 2018). Strikingly, the colocalization of mRNA ends was observed in cells in which the eIF4G•PABP interaction was disrupted by mutagenesis (Adivarahan et al, 2018). Based on these experiments, it was concluded that, in the absence of helicase activity of translating ribosomes, mRNA ends come in close proximity because of intramolecular basepairing interactions within mRNA (Adivarahan et al, 2018;Khong & Parker, 2018).…”
Section: Mrna Compactness and The Closed-loop Model Of Translation Inmentioning
confidence: 97%
See 2 more Smart Citations